THE EFFECT OF POE STRATEGY ON STUDENTS’ CONCEPTUAL CHANGE REGARDING WATER DENSITY - Rida Yulianti; Andi Suhandi; Wahyu Sopandi (JPSD (Jurnal Pendidikan Sekolah Dasar), 2020)
The purpose of this study was to understand the effect of Predict Observe and Explain (POE) strategy toward students’ conceptual change about density of water. This study was conducted because many students have a conception which is not in accordance with the scientific conception of the water. The subjects used in this study were 34 students on 5th grade students in one of primary schools in Bekasi. Research method was pre-experiment method and the design is One-Group Pretest-Posttest Design. The instrument used to view the level of student’s conceptual change was a pretest and posttest with four-tier diagnostic test. Test answers were then will be adjusted to conceptual change category consisting of five levels of conceptual change are construction, revision, complementation, static, and disorientation. The results showed that conceptual changes in students given treatment using POE strategy were at the construction level 2% (students were able to construct their understanding), revision 84% (students were able to make improvements (revisions) to their initial understanding), and static as much 14% (Students cannot change their understanding to a better understanding). These results show that the majority of students experience conceptual change after learning to use the POE strategy. Keywords: Strategy; POE; Conceptual Change